PENGARUH WORK-LIFE BALANCE DAN KOMPENSASI TERHADAP KEPUASAN KERJA PELAKU PARIWISATA SUMATERA SELATAN - Efan Elpanso; Agus Yuliansah Saputra (Universitas Bina Taruna Gorontalo, 2024)
This study aims to determine the effect of Work-Life Balance and work compensation on Job Satisfaction of Tourism Actors in South Sumatra. The research method used is a quantitative approach. The number of samples in this research is 106 employees. Data collection techniques used were observation and questionnaires. The results showed that 1) there was a significant influence between Work-Life Balance on job satisfaction, this shows that Work-Life Balance has a positive effect on job satisfaction 2) There is a positive effect on compensation on job satisfaction. 3) Work-Life Balance and compensation simultaneously have a positive effect on job satisfaction. The effect of the variables Work-Life Balance (X1) and compensation (X2) on job satisfaction (Y) can be explained by 74.0% while 26.0% is influenced by other variables outside this regression equation such as promotion, brand image and purchasing decisions